Análise dos processos-crimes de defloramento e estupro envolvendo mulheres negras em Santa Maria-RS (1910-1940) - Martins, Bruno dos Santos (2020)
The present dissertation analyzes criminal processes of Deflowering and Rape occurred from 1918 to 1942, in the city of Santa Maria (RS), involving black women. The discussion around female virginity involved several intellectuals from the turn of the 18th to the 19th century, for them, the woman should be demure and work for the home, preserving herself to marriage. The hymen was the main indication of virginity and honesty, and women who were victims of Deflowering and Rape used the judicial apparatus to restore their honor and the honor of their families. These processes provide information that helps to understand that there was a "moral" and "good manners" of society at that time. This research aims to analyze the statements of those involved in the Defloration and Rape processes to understand the mentality of that moral present in the context of those women.